SAT0573 HEALTHCARE RESOURCE UTILISATION AMONG PATIENTS DIAGNOSED WITH SYSTEMIC SCLEROSIS-ASSOCIATED INTERSTITIAL LUNG DISEASE IN ENGLAND. (June 2019) - Gayle, Alicia; Schoof, Nils; Alves, Margarida; Clarke, Deborah; Raabe, Christina; Das, Prithwiraj; Maher, Toby
Abstract : Background: Systemic sclerosis-associated interstitial lung disease (SSc-ILD) places a substantial burden on patients and on healthcare services. Despite this, assessments of healthcare resource utilisation and costs incurred during the management of SSc-ILD are limited. Objectives: To assess healthcare resource utilisation and costs among patients with SSc-ILD compared with SSc overall and patients with SSc and other organ involvement (SSc-OOI). Methods: This was a population-based cohort study. Routinely collected healthcare data were extracted from medical records (dated 1 January 2005 to 31 March 2016) in the Clinical Practice Research Datalink (CPRD) and the Hospital Episode Statistics (HES) databases. Patients with SSc, with or without ILD and/or OOI, were identified from primary and secondary care records in combination with modified European League Against Rheumatism (EULAR) classification criteria. Patients were included in the OOI sub-cohort if their SSc affected cardiac, gastrointestinal, renal or oral function. Eligible patients were aged at least 18 years at first diagnosis, were diagnosed within the study period, and had at least 12 months of available data in CPRD/HES before and after diagnosis. All-cause healthcare resource utilisation (inpatient stays; A&E attendances; outpatient visits; general practitioner visits) and costs among patients with SSc, SSc-ILD and SSc-OOI were calculated to 2016 GBP. Medication costs were not included. Predictors of total healthcare costs were estimated using a multivariate generalised linear model, with a gamma distribution and log link function to allow for non-normal distributed costs. Comorbid diseases were categorised using the Charlson Comorbidity Index. Results: Of 675 patients with SSc, 127 (19%) had ILD and 477 (71%) had OOI; a subset of 103 (15%) patients had both ILD and OOI. The remaining 174 patients (26%) had SSc without ILD or OOI. Median (interquartile range) annual healthcare costs per patient were: £2, 601 (£962–6, 885) in SSc; £3, 449 (£1, 271–8, 717) in SSc-OOI; £5, 899 (£2, 986–13, 905) in SSc-ILD; £6, 375 (£3, 046–15, 041) in SSc-ILD-OOI. Patients with SSc-ILD (with or without OOI) had the highest rates of inpatient stays, outpatient visits, A&E attendances, and general practitioner visits per person-year. Inpatient stays alone accounted for >60% of the total healthcare costs among SSc patients with ILD (median cost >£3, 600 per patient per year). Each patient with SSc-ILD had, on average, 10 outpatient visits per year, at a total yearly median cost of >£840. In comparison, patients with SSc-OOI averaged 7 outpatient visits at a total yearly median cost of £615. Characteristics significantly associated with higher yearly healthcare costs among SSc patients were: older age at diagnosis, diagnosis of anaemia, and number of comorbid diseases. Conclusion: The annual healthcare cost for a patient with SSc-ILD is substantial (£2, 986–13, 905), with inpatient stays the major cause of costs, and is much higher than for patients with SSc-OOI (without ILD). Healthcare costs are also higher among older SSc patients and those with more comorbidities. These results quantify the economic burden of SSc-ILD in a real-world setting, which will be useful when evaluating the cost-effectiveness of new treatment options for SSc-ILD. There is an unmet need for effective therapies for SSc-ILD. Acknowledgement: Funding: Boehringer Ingelheim International GmbH, Germany Disclosure of Interests: Alicia Gayle Employee of: Employee of Boehringer Ingelheim, Nils Schoof Employee of: Employee of Boehringer Ingelheim, Margarida Alves Employee of: Employee of Boehringer Ingelheim, Deborah Clarke Employee of: Employee of Boehringer Ingelheim, Christina Raabe Employee of: Employee of Boehringer Ingelheim, Prithwiraj Das Employee of: Employee of Boehringer Ingelheim, Toby Maher Grant/research support from: Received funds from BI advisory board participation and conference travel. Received research funding and/or consulting fees or other remuneration from GSK, UCB, AstraZeneca, Roche, Bayer, Biogen Idec, Cipla, Prometic, and Sanumed. Toby Maher has, via his institution, received industry-academic funding from GlaxoSmithKline R&D and UCB., Consultant for: Toby Maher has received consultancy or speakers fees from Apellis, AstraZeneca, Bayer, Biogen Idec, Boehringer Ingelheim, Galapagos, GlaxoSmithKline R&D, Indalo, Pliant, ProMetic, Roche, Samumed and UCB; and has received consultancy fees from Galecto.